Advances in Biomimetics: The Power of Diversity - Stanislav N. Gorb; Giuseppe Carbone; Thomas Speck; Peter Fratzl (Biomimetics)
Biomimetics research on living systems attempts to transfer their properties and functions to engineering applications [...]